A study of macroinvertebrate communities in Bolshiye Koty Bay of Lake Baikal using DNA metabarcoding - L. S. Kravtsova; T. E. Peretolchina; T. I. Triboy; I. A. Nebesnykh; A. E. Tupikin; M. R. Kabilov; Л. С. Кравцова; Т. Е. Перетолчина; Т. И. Трибой; И. А. Небесных; А. Е. Тупикин; М. Р. Кабилов (Institute of Cytology and Genetics of Siberian Branch of the RAS, 2023)
The diversity of macroinvertebrates, the structure of their communities in Bolshiye Koty Bay (Lake Baikal) was studied by a DNA metabarcoding approach using an Illumina MiSeq system. Internal primer mlCOIintF in combination with jgHCO2198 of the Folmer fragment of the COI gene were used for macroinvertebrate metabarcoding. A total of 118009 reads of the COI gene fragment (at least 313 bp in length) were obtained. The correlation of the Spearman coefficient (S = 0.6, p < 0.05) with the abundance of macroinvertebrates in the samples before DNA extraction showed that the number of reads can serve as an indirect characteristic of the abundance of a species (operational taxonomic unit, OTU). 115 OTUs belonging to the higher taxa of macroinvertebrates were identified: Porifera, 1; Platyhelminthes, 3; Annelida, 38; Arthropoda, 55; Mollusca, 18. At a high level of resolution (with homology with GenBank reference sequences ≥ 95 %, coverage ≥ 90 %), 46 taxa of macroinvertebrates comprising three communities were registered: one dominated by molluscs (Choanomphalus conf. maacki) and two dominated by chironomids (Orthocladius grega rius Linev., Sergentia baicalensis Tshern.). Communities are characterized by low species diversity according to Shannon (from 0.7 to 1.2 bits), high concentration of dominance according to Simpson (from 0.5 to 0.7) and low evenness according to Pielou (from 0.3 to 0.4). Dominants and subdominants in the communities account for 91 to 96 % of COI gene fragment reads. The spatial distribution of the dominant species identified in the communities is influenced by the geomorphological features of the bottom and the composition of sediments in the area studied. The approach proposed for studying the structure of macroinvertebrate communities based on DNA metabarcoding and next generation sequencing can be recommended for express assessment of the state of aquatic ecosystems in the monitoring. Приводятся сведения о разнообразии макробеспозвоночных животных, структуре их сообществ в бухте Большие ...